Studying English by Social Media “Students’ Perception” (Case Study the Fifth Semester STIKOM Tunas Bangsa Pematangsiantar) - Ika Purnama Sari; Anita Purba; Epi Supriyani Siregar; Iin Parlina; Rizky Khairunnisa Sormin (Athena: Journal of Social, Culture and Society, 2025)
This study shows that social media has a significant role in improving English skills, especially in terms of learning and communication. Social media provides a platform for informal and enjoyable English learning, and encourages interaction and collaboration between users. Social media plays an important role in English learning because it provides access to various learning resources, encourages social interaction, and improves speaking skills. By utilizing platforms such as YouTube, Instagram, and Facebook, students can access educational content, participate in discussions, and practice English interactively. According to student perceptions, YouTube is a very good social media for improving English skills. Almost most students in the fifth semester of STIKOM Tunas Bangsa  Pematangsiantar like to learn English using YouTube. This is because YouTube provides various types of English content that can help improve listening, speaking, reading, and writing skills. In addition, many YouTube channels are specifically created for English learning, with materials presented in an easy and interesting way.